HERITAGE TOURISM AND LOCAL ECONOMIC TRANSFORMATION IN BUKITTINGGI NAVIGATING FORMAL AND INFORMAL LIVELIHOODS - Ucu Feni; Adri Febrianto; Azmi Fitrisia (Indonesian Journal of Social Science Education (IJSSE), 2026)
This article aim to explain the heritage tourism is widely recognized as a driver of regional economic growth, limited research has examined how historical tourism clusters reshape the daily livelihoods of micro-entrepreneurs in secondary heritage cities. This study investigates how heritage tourism transforms the local economy surrounding four major landmarks in Bukittinggi, Indonesia: Jam Gadang plaza, the Birth House of Bung Hatta, Fort de Kock, and the Lobang Jepang tunnel. Using a qualitative descriptive approach, this study interviewes twelve key informants—including street vendors, craft merchants, local guides, and tourism officials—and combined these narratives with field observations and documentary analysis. The thematic findings reveal that the local tourism economy depends on a symbiotic relationship between formal institutional regulation and informal grassroots trade. Local residents gradually shifted from unstable low-wage labor into tourism-related services, generating higher but highly seasonal incomes. The transformation is further accelerated by the adoption of digital payment systems such as Quick Response Code Indonesian Standard (QRIS). This study introduces the Hybrid-Formal-Informal Tourism Economy Model to explain how informal micro-vendors survive and adapt within institutional heritage spaces. The findings contribute to contempary debates on inclusive urban tourism governance in secondary heritage cities. The study concludes that municipal governments must implement balanced  zoning policies that protect informal livelihoods while preserving the visual and physical authenticity of heritage monuments from commercial overcrowding.